A pot line rectiformer scheme with hybrid-shunt active power filter - Fadhel Abbas Albasri; Sayed Ali Al-Mawsawi; Mahmood Al-Mahari (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Passive harmonic filters (PHF) are commonly used in conventional potline rectifier transformers (Rectiformer) schemes of aluminum smelters to improve the power quality and reduce harmonic distortions to an acceptable level. However, changes in operating conditions and system configuration affect the performance capability of PHF in attenuating harmonics. In this paper, a Rectiformer scheme with hybrid-shunt active power filter (SAPF) is used instead of PHF and compared with the other commonly applied schemes in aluminum smelter in terms of harmonic attenuation capability. The SAPF potline Rectiformer scheme and other schemes are modeled and simulated using MATLAB/Simulink.  A control strategy suitable for potline load behavior is furnished in this paper for SAPF. The simulation results reveal the performance superiority of the proposed SAPF as compared to the conventional and ALBA pot line (PL) 6 schemes.